Rural smallholder milk production and utilization and the future for dairy development in Ethiopia - O'Connor, C.B. (International Livestock Centre for Africa, 1992)
Reviews the rural smallholder milk production and utilisation in Ethiopia and discusses the future for dairy development. Looks into the smallholder milk processing techniques in the highlands of Ethiopia. It is found that milk produced by smallholders is used for family consumption and the production of butter and a cottage-type cheese. For butter making, milk is collected over a period of three or four days in a clay pot. When the milk has soured and sufficient milk has been collected, the pot is shaken back and forth until butter granules are formed. The buttermilk remaining after the butter is separated from the whole milk is used to produce a cottage type cheese by heating the buttermilk and separating the coagulated fat and protein from the whey. The various options and outlets for milk and milk products available to rural smallholder milk producers are shown. There is constant competition between calves and members of the family for liquid milk and to a lesser extent there is competition between family requirements for liquid milk and liquid milk to be processed into butter and cheese for sale.